NCSB2024: 22nd Nordic conference on small business research. Conference proceedings - (:unkn) unknown (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2024)
The 22nd Nordic Conference on Small Business Research (NCSB2024) was organized in Turku, Finland on May 29-31, 2024. NCSB conference is one of the oldest conferences in entrepreneurship and small business research in the world, with the first conference being held already in 1980. Since its inception the NCSB conference has been a biannual event in the Nordic tradition characterized by an open atmosphere that encourages the exchange of ideas between researchers within the field of small business and entrepreneurship. There were 101 abstracts submitted to this year’s conference either to one of the six special tracks or to the open track. In the final programme, there were 65 papers presented. This conference proceedings publication brings together the 9 full revised papers submitted for the proceedings after the conference. They give you an interesting glimpse into the diversity of research and multiple perspectives of research presented during the conference. We trust that you will see a lot more of the papers presented published in journals, research books and dissertations in the years to come.